Supply chain information technology - Olson, David Louis (New York, NY : Business Expert Press, 2012)
The target market for this book is practitioners in the supply chain management field, one of the fastest growing fields in our economy. The rapid growth in computer technology provides supply chain managers with valuable tools to better coordinate and control their operations. This book seeks to describe systems available to give supply chains information system support, demonstrating key tasks with demonstrated analytic techniques.
Includes bibliographical references (p. 113-117) and index.
Keywords: Business logistics -- Data processing